2013
DOI: 10.1682/jrrd.2012.05.0098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 6-minute walk test performance between male Active Duty soldiers and servicemembers with and without traumatic lower-limb loss

Abstract: Abstract-The rehabilitation of U.S. military servicemembers (SMs) who have sustained a traumatic loss of one or both lower limbs requires outcome measures that can assess their physical capabilities in comparison with their uninjured colleagues. Describing reference ranges for the 6-minute walk test (6MWT) in both populations will help clinicians develop appropriate goals for rehabilitation and document progress toward those goals. A convenience sample of 118 male U.S. SMs with and 97 without traumatic lower-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
1
16
1
2
Order By: Relevance
“…In contrast to significant changes in outdoor walking speed noted by previous authors [42,45] when participants with TFA wore a knee with an adaptive control system, adaptive control in this study did not significantly alter participants' time to complete the walking course (nor did it reduce their perceived physical or mental exertion). Results here are more similar to findings reported by Linberg et al, who found no significant differences in 6 min walk distances in servicemembers who wore both microprocessor (adaptive) and nonmicroprocessor (passive) knees [97]. Thus, it may be that adaptive knee technology is more effective at facilitating walking over shorter distances (i.e., <250 ft [75 m]) than walking longer distances (i.e., >0.5 mi [880 m]).…”
Section: Out-of-laboratory Performance Outcomessupporting
confidence: 91%
“…In contrast to significant changes in outdoor walking speed noted by previous authors [42,45] when participants with TFA wore a knee with an adaptive control system, adaptive control in this study did not significantly alter participants' time to complete the walking course (nor did it reduce their perceived physical or mental exertion). Results here are more similar to findings reported by Linberg et al, who found no significant differences in 6 min walk distances in servicemembers who wore both microprocessor (adaptive) and nonmicroprocessor (passive) knees [97]. Thus, it may be that adaptive knee technology is more effective at facilitating walking over shorter distances (i.e., <250 ft [75 m]) than walking longer distances (i.e., >0.5 mi [880 m]).…”
Section: Out-of-laboratory Performance Outcomessupporting
confidence: 91%
“…Linberg et al found demographics (i.e., height, weight) did not affect the six-minute walk test (6MWT) (12). This is consistent with previous reports in finding that, when adjusting for medical comorbidities, age, and sex, BMI was not a significant predictor of walking ability (5).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent a minor amputation were more likely to ambulate with or without assistance but less so than patients who did not have an amputation after lower extremity bypass (23). Linberg et al., in a high quality article, reported a significant difference in 6MWT performance between bilateral TTA patients and TFA patients, with bilateral TTA patients walking further (12). Chin et al reported, in a medium quality study, solely on the hip disarticulation amputee (HDA), where older HDA patients in good physical condition and with a low prevalence of comorbidities were able to successfully walk with a prosthesis in a community setting (10).…”
Section: Discussionmentioning
confidence: 99%
“…After completing their military rehabilitation pathway, 35 (64%) were able to walk distances comparable to age-matched healthy controls (459e738m) 14 (unilateral amputee, nZ14, 78%; nonoperationally injured unilateral amputee, nZ8, 80%; bilateral amputee, nZ11, 52%; triple amputee, nZ2, 33%) and 85% of amputees were able to walk or run independently. Linberg et al 15 reported 6MWD in a large cohort of US service members and veterans. They reported a greater mean 6MWD in their cohort (503e661m).…”
Section: Discussionmentioning
confidence: 99%